2016
DOI: 10.1055/s-0036-1572121
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for risk stratification in pulmonary arterial hypertension

Abstract: Risk stratification in pulmonary arterial hypertension (PAH) is paramount to identifying individuals at highest risk of death. So far, there are only limited parameters for prognostication in patients with PAH.95 patients with confirmed PAH were included in the present analysis and followed for a total of 4 years. Blood samples were analysed for serum levels of N-terminal pro-brain natriuretic peptide, highsensitivity troponin T (hsTnT), pro-atrial natriuretic peptide ( proANP), growth differentiation factor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…They found that higher GDF-15 levels were associated with the 4-year mortality risk. However, GDF-15 was not a better prognosticator than NT-proBNP, high-sensitive troponin-T and proatrial natriuretic peptide in their study 22…”
Section: Discussionmentioning
confidence: 69%
“…They found that higher GDF-15 levels were associated with the 4-year mortality risk. However, GDF-15 was not a better prognosticator than NT-proBNP, high-sensitive troponin-T and proatrial natriuretic peptide in their study 22…”
Section: Discussionmentioning
confidence: 69%
“…Four studies in PAH or PAH plus chronic thromboembolic pulmonary hypertension used receiver operating characteristic curve analysis to identify threshold values to predict survival in treatment naïve patients. 9,10,13,14 Cutoff values of 705 ng/L (n=95, Zelniker et al 14 ), 1256 ng/L (n=161, Mauritz et al 13 ), 1400 ng/L (n=55, Fijalkowska et al 9 ), and 1800 ng/L (n=109, Nickel et al 10 ) were identified. Although generally in the range of the high-risk cutoff used in the current guidelines (>1400 ng/L), 5 considerable variability was seen.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the lowest-risk tier in the current guidelines, an NT-proBNP level <300 ng/L, 5 was not initially identified in PAH receiver operating characteristic curve analysis (although it is used in excluding acute heart failure in other settings 23 ). Limitations of the current thresholds therefore include the small samples sizes, the lack of separate validation cohorts, the inclusion of only treatment-naïve patients, the variability in the thresholds identified in receiver operating characteristic analyses 9,10,13,14 and the lack of studies specifically designed to identify cutoffs for 3 tiers of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of death at 2 years was increased among patients with higher BNP at baseline [40]. At 4 years, risk of death was increased among patients with NT-proBNP > 704.5 pg/mL at baseline [43]. Increased risk of death at 5 years was associated with baseline levels of BNP > 340 pg/mL [52].…”
Section: Bnp/nt-probnp and Risk Of Deathmentioning
confidence: 90%